Reply to Stedman Vol. 4 No. 1 - David C. Berliner; Bruce J. Biddle (Arizona State University, 1996)
Berliner and Biddle answer Lawrence Stedman's review of their book The Manufactured Crisis, which was published in the Education Policy Analysis Archives as Volume 4, Number 1, 1996.